A Novel Automated Construction Scheme for Efficiently Developing Cloud Manufacturing Services - Chen, Chao-Chun; Hung, Min-Hsiung; Li, Po-Yi; Lin, Yu-Chuan; Liu, Yu-Yang; Cheng, Fan-Tien (IEEE robotics and automation letters, 2018)
Cloud manufacturing (CMfg) has emerged as a next-generation manufacturing paradigm that has potential to revolutionize the manufacturing industry. In further promotion of CMfg, how to build CMfg services in an automatic and efficient manner is an essential and challenging subject. Currently, there is no literature addressing such issue. Aimed at facilitating rapid construction of CMfg services, this letter proposes a novel automated construction scheme for developing CMfg services, called Manufacturing Service Automated Construction Scheme (MSACS). First, we develop a three-phase workflow of MSACS to address the issues of how to construct CMfg services automatically using standalone software library package (SSLP). Next, we design a system architecture of MSACS to delineate how to implement MSACS. Then, we depict the designs of MSACS's core components. Finally, we apply MSACS to conduct industrial case studies to build the automatic virtual metrology cloud service and intelligent yield management cloud service for an intelligent manufacturing platform. Testing results demonstrate that MSACS can automatically construct the target CMfg services in a very efficient manner after uploading the required SSLPs. Thus, MSACS can significantly alleviate the burden of engineers in building CMfg services, and in turn can facilitate the promotion of CMfg.